Optimization of Production System: An Application of Total Productive Maintenance (TPM) - Chukwutoo, C. Ihueze; Paschal, S. Ebisike (Archives of Current Research International, 2018)
In today’s trends of market competition, Production Company is moving towards improving and optimizing of their products in order to remain competitive. Total productive maintenance (TPM) is one the most ideal maintenance management program to ensure high system availability, since (TPM) is consider as a sub-part of Lean Manufacturing. In this work, research has been conducted to study the impact of equipment effectiveness, availability and performance through the use of total productive maintenance in Apex Automated Manufacturing Industry, with the objectives of producing goods without reducing product quality, increasing product cost and to produce a low batch quantity of products at the earliest possible time with non defective products. The equipment parameters, such as the availability rate, the performance and the quality rates of the goods produced are consider while optimizing the Equipment Effectiveness (EE) of a production system. Pareto principle and statistical models of downtimes were used to depict the most downtime factors. This study reported OEE of 22.4% and 23.5% for 2012 and 2013 years respectively as regards to the world class recommended OEE is 85%. Pareto analysis showed that planned maintenance and machine failure / breakdown caused about 80% of total downtime. And the management and maintenance group should always target total implementation of the eight pillars of TPM to bring the value of OEE to world class standard of 85%.